Who is a “knowledge worker” – clarifying the meaning of the term through comparison with synonymous and associated terms - Surawski Bartosz (Management, 2019)
The term “knowledge worker” has entered the language of management and economics, becoming popular or even fashionable. Consequently, its definitions are varied and often ambiguous or provisional – which makes it difficult to identify and research such employees. Deeper understanding of the term “knowledge workers” is required.